IMPLEMENTASI PROGRAM GERAKAN LITERASI SEKOLAH DALAM MENINGKATKAN MINAT BACA SISWA KELAS VIII UPT SPF SMP NEGERI 1 MAKASSAR: IMPLEMENTATION OF THE SCHOOL LITERACY MOVEMENT PROGRAMME IN INCREASING STUDENTS' INTEREST IN READING CLASS VIII UPT SPF SMP NEGERI 1 MAKASSAR - Aulia Putri, Fadilah Pramestiyani; Nensilianti; Usman (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research is entitled Implementation of the School Literacy Movement Program in Increasing Reading Interest in Class VIII UPT SPF Students at SMP Negeri 1 Makassar. The aim of this research is to describe the forms of school literacy movement activities in increasing reading interest, interest in reading, and students' perceptions of the school literacy movement in class VIII UPT SPF SMP Negeri 1 Makassar. This research is of qualitative type with a descriptive research design. The results of the research show that the implementation of the school literacy movement program at SMP Negeri 1 Makassar has been carried out with various activities, namely the Reading Movement 15 minutes before class, the existence of a reading room, a special literacy day (amazing reading Friday), literacy activities outside of school (Pore Goes to Park), touch the library, reading bills in the form of daily journals, the role of teachers as role models, and providing literacy campaign posters.